2006
DOI: 10.1136/jmg.2005.039743
|View full text |Cite
|
Sign up to set email alerts
|

Association of lung function decline with the heme oxygenase-1 gene promoter microsatellite polymorphism in a general population sample. Results from the European Community Respiratory Health Survey (ECRHS), France

Abstract: Inducible heme oxygenase (HO-1) acts against oxidants that are thought to play a major role in the pathogenesis of chronic obstructive pulmonary disease (COPD), characterised by impaired lung function. A (GT) n repeat polymorphism in the HO-1 gene promoter can modulate the gene transcription in response to oxidative stress. We hypothesised that this polymorphism could be associated with the level of lung function and decline in subjects exposed to oxidative agression (smokers). We genotyped 749 French subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
60
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 27 publications
7
60
1
1
Order By: Relevance
“…Results from the European Community respiratory health survey in France showed that long HO-1 gene promoter (GT) n repeats in heavy smokers are associated with susceptibility to develop lung dysfunction and airway obstruction (Guénégou et al, 2006). Lung dysfunction as a result of lung cancer was seen in Japanese patients with long GT repeats of HO-1; however, this effect was limited to male patients (Kikuchi et al, 2005).…”
mentioning
confidence: 89%
“…Results from the European Community respiratory health survey in France showed that long HO-1 gene promoter (GT) n repeats in heavy smokers are associated with susceptibility to develop lung dysfunction and airway obstruction (Guénégou et al, 2006). Lung dysfunction as a result of lung cancer was seen in Japanese patients with long GT repeats of HO-1; however, this effect was limited to male patients (Kikuchi et al, 2005).…”
mentioning
confidence: 89%
“…For comparability with previous studies showing associations of o33 repeats with lung function [7,8], repeat genotypes were classified as having at least one long allele (o33 repeats) or not. The allele distribution in the study population is presented in figure 2.…”
Section: Genotyping Proceduresmentioning
confidence: 99%
“…a genetic variant consisting of a variable number of short nucleotide sequence repetitions (in this case ''GT''), is known in the promoter region of the HMOX1 gene. In general population samples from France and the Netherlands, long repeat alleles (o33 repeats) were associated with accelerated decline in several lung function parameters, especially among smokers [7,8].…”
mentioning
confidence: 98%
“…SNPs in classical NFE2L2 targets such as glutathione S-transferase (GST) genes, NAD(P)H quinone oxidoreductase (NQO1), glutamate-cysteine ligase catalytic subunit (GCLC), and heme oxygenase-1 (HMOX1) have previously been shown to be associated with COPD (7,18,20,21,29,33,44,55,56,65,69). In contrast, other studies failed to find association of these genes with COPD-related phenotypes (23,24,57,67,68).…”
Section: Discussionmentioning
confidence: 83%